Analysis of the completeness of indicators of soil assessment in Ukraine based on materials of the Institute of land management of the UAAS - Patiyuk, O. (Land Management, Cadastre and Land Monitoring, 2020)
Taking into account the fact that the soil appraisal data is the basis for the economic valuation of agricultural land, and the data on the economic valuation of land is the basis for the normative monetary valuation of land plots, that is, there is a single, continuous methodological process of land valuation in which the data are unreliable in the first stage generates calculation errors in the following stages.Since the issue of soil appraisal in the conditions of market land relations does not lose its relevance, and taking into account that the last time work on soil appraisal of agricultural lands in Ukraine was carried out in 1993, and over the past quarter century, formally, should already be carried out, at least three new soil appraisal tours, as it is prescribed in the Law of Ukraine “On land valuation”, but in fact, the soil appraisal indicators were not updated for various reasons.The authors analyzed the database of soil assessment in Ukraine according to 1993 scales, as well as the explications of agro-industrial groups of soils of natural agricultural regions (NAR) for the stock materials of the Institute of Land Management of the UAAS, on the basis of which an attempt was made to determine the completeness of the soil cover of the NAR of Ukraine for the indicators of assessment .The study shows that the indicators of soil appraisal on the materials of the Institute of Land Management of the UAAS in their completeness far from always can serve as the basis for a continuous monetary assessment of agricultural land and require research using new approaches and developments.Key words: soil bonitet, economic assessment of agricultural production groups of soils, soil assessment, agricultural land.